The effects of collagen-rich extracellular matrix on the intracellular delivery of glycol chitosan nanoparticles in human lung fibroblasts - Yhee JY (Dove Medical Press, 2017)
Ji Young Yhee,1 Hong Yeol Yoon,2 Hyunjoon Kim,3 Sangmin Jeon,2 Polla Hergert,1 Jintaek Im,1 Jayanth Panyam,3 Kwangmeyung Kim,2,4 Richard Seonghun Nho1 1Department of Medicine, University of Minnesota, Minneapolis, MN, USA; 2Center for Theragnosis, Biomedical Research Institute, Korea Institute of Science and Technology, Seoul, Republic of Korea; 3Department of Pharmaceutics, University of Minnesota, Minneapolis, MN, USA; 4Korea University-Korea Institute of Science and Technology (KU-KIST) Graduate School of Converging Science and Technology, Korea University, Seoul, Republic of Korea Abstract: Recent progress in nanomedicine has shown a strong possibility of targeted therapy for obstinate chronic lung diseases including idiopathic pulmonary fibrosis (IPF). IPF is a fatal lung disease characterized by persistent fibrotic fibroblasts in response to type I collagen-rich extracellular matrix. As a pathological microenvironment is important in understanding the biological behavior of nanoparticles, in vitro cellular uptake of glycol chitosan nanoparticles (CNPs) in human lung fibroblasts was comparatively studied in the presence or absence of type I collagen matrix. Primary human lung fibroblasts from non-IPF and IPF patients (n=6/group) showed significantly increased cellular uptake of CNPs (>33.6–78.1 times) when they were cultured on collagen matrix. To elucidate the underlying mechanism of enhanced cellular delivery of CNPs in lung fibroblasts on collagen, cells were pretreated with chlorpromazine, genistein, and amiloride to inhibit clathrin-mediated endocytosis, caveolae-mediated endocytosis, and macropinocytosis, respectively. Amiloride pretreatment remarkably reduced the cellular uptake of CNPs, suggesting that lung fibroblasts mainly utilize the macropinocytosis-dependent mechanism when interacted with collagen. In addition, the internalization of CNPs was predominantly suppressed by a phosphoinositide 3-kinase (PI3K) inhibitor in IPF fibroblasts, indicating that enhanced PI3K activity associated with late-stage macropinocytosis can be particularly important for the enhanced cellular delivery of CNPs in IPF fibroblasts. Our study strongly supports the concept that a pathological microenvironment which surrounds lung fibroblasts has a significant impact on the intracellular delivery of nanoparticles. Based on the property of enhanced intracellular delivery of CNPs when fibroblasts are made to interact with a collagen-rich matrix, we suggest that CNPs may have great potential as a drug-carrier system for targeting fibrotic lung fibroblasts. Keywords: cellular uptake, glycol chitosan nanoparticles, idiopathic pulmonary fibrosis, macropinocytosis, type I collagen matrix